Royal Malaysia Police Hulu Selangor District / Muhammad Fadhli Amran - Amran, Muhammad Fadhli (Universiti Teknologi MARA, Sarawak, 2016)
Royal Malaysia Police was formed in 25 March 1807 (Royal Malaysia Police, 2016). Its headquarters are located at Bukit Aman, Kuala Lumour. The Royal Malaysia police led by an Inspector General of Police (IGP) Tan Sri Khalid Abu Bakar. The constitution, control, employment, recruitment, funding, discipline, duties and powers of the police force are specified and governed by the police act 1967 (Royal Malaysia Police, 2016). In carrying out its responsibilities, the regular RMP is also assisted by a support group of Extra Police Constables, Police Volunteer Reserves, Auxiliary Police, Police Cadets and civilian service element (Royal Malaysia Police, 2016). The Royal Malaysia Police consist of nine department involved crime prevention which is Criminal Investigation Department, Narcotic Criminal Investigation Department, Internal Security and Public Order Department, Special Branch, Commercial Crime Investigation Department and Counter Terrorism Special Operation Team. The administration involved of Management Department and Strategic Resources and Technology Department. These department led by the Commissioner of Police.